Microbial Ecology of French Dry Fermented Sausages and Mycotoxin Risk Evaluation During Storage - Coton, Monika; Deniel, Franck; Mounier, Jérôme; Joubrel, Rozenn; Robieu, Emeline; Pawtowski, Audrey; Jeuge, Sabine; Taminiau, Bernard; Daube, Georges; Coton, Emmanuel; Frémaux, Bastien (Frontiers in Microbiology, 2021)
Dry fermented sausages are produced worldwide by well-controlled fermentation processes involving complex microbiota including many bacterial and fungal species with key technological roles. However, to date, fungal diversity on sausage casings during storage has not been fully described. In this context, we studied the microbial communities from dry fermented sausages naturally colonized or voluntarily surface inoculated with molds during storage using both culture-dependent and metabarcoding methods. Staphylococci and lactic acid bacteria largely dominated in samples although some halotolerant genera (e.g. Halomonas, Tetragenococcus, Celerinatantimonas spp. ) were also frequently observed. Fungal populations varied from 7.2 to 9.8 log TFU/cm2 sausage casing during storage, suggesting relatively low count variability among products. Fungal diversity identified on voluntarily-inoculated casings was lower (dominated by Penicillium nalgiovense and Debaryomyces hansenii) than naturally environment-inoculated fermented sausages (colonized by P. nalgiovense, P. nordicum, other Penicillium spp., and sporadically Scopulariopsis sp., D. hansenii and Candida zeylanoïdes). Penicillium nalgiovense and D. hansenii were systematically identified highlighting their key technological role. The mycotoxin risk was then evaluated and in situ mycotoxin production of selected mold isolates was determined during pilot scale sausage productions. Among the identified fungal species, P. nalgiovense was confirmed not to produce mycotoxins. However, some P. nordicum, P. chrysogenum, P. bialowienzense, P. brevicompactum and P. citreonigrum isolates produced one or more mycotoxins in vitro. P. nordicum also produced ochratoxin A during pilot-scale sausage productions using “worst-case” conditions in the absence of biotic competition. These data provide new knowledge on fermented sausage microbiota and the potential mycotoxin risk during storage.